EFEKTIVITAS PEMUNGUTAN PAJAK PENGAMBILAN GALIAN - Saptudis '; Abdul Sadad (Universitas Riau, 2013)
The purpose of this study is toinvestigate and analyze the factors that influence the effectiveness of tax collection excavationtaking class C Singingi Kuantan District. This research was conducted at the District RevenueOffice Singingi Kuantan, where the informant resnponden and research studies is an employee inthe Office Pendapayan Singingi Kuantan district and taxpayers making excavation group C. Datawas collected through questionnaire dissemination techniques, interviews and observations,once the data is collected and then analyzed using qualitative descriptive analysis. The resultshowed that the effectiveness of tax collection excavation taking class C in Kuantan DistrictSingingi then concluded quite well. Discovered factors that influence the effectiveness of taxcollection making excavation category C is a factor of division of labor and human factors.